Inhibitory effect of Scutellaria pinnatifida Extracts on the Alpha synuclein Cytotoxicity - Mahdieh Sashourpour; Dina Morshedi; Saber Zahri; Farhang Ali akbari; Marzieh Fottovat; Tayebeh Rajabian (Institue of Medicinal Plants, ACECR, 2019)
Many of neurodegenerative diseases (NDs) are associated with formation of the protein aggregates called amyloidal fibrils. Fibrillization of alpha-synuclein seems to be a key stage in the creation and progression of NDs and finding the compounds that inherent the toxicity of alpha-synuclein aggregates seems to be one of the most attention subjects in the neurodegenerative studies.  In this study, the effects of various extracts derived from the roots of S. pinnatifida, on the alpha-synuclein cytotoxicity were assayed. In this regard, the process of fibrillization was induced in alpha-synuclein and then formation of aggregates was verified using standard methods such as thioflavin T fluorescence assay and microscopic fluorescence images. Neurotoxicity of alpha-syncline fibrils on PC12 cells was examined by MTT and LDH methods. Results showed that, after treatment with alpha-synuclein aggregates, the rate of cell death was evaluated significantly. In spite of  the methanolic, hexane and ethyl acetate extracts, in the presence of dichloromethane and n.butanol extracts, the death of cells treated with alpha-synuclein were inhibited significantly. Furthermore, it was found that dichloromethane and n.butanol extracts contained high amount of anti-oxidant flavonoids. It can be concluded that the extracts of S. pinnatifida, significantly inhibit the harmful effects of toxic alpha-synuclein aggregates and can be used to treat amyloid-related disorders. However, it is required more investigations on the kind of the effective compounds of S. pinnatifida extracts.